Emergency Department Patient Satisfaction Survey in a Tertiary Care Hospital of Eastern Nepal - Poudel, Masum; Bhandari, Rabin; Uprety, Samyog; Chaudhary, Ritesh; Yadav, Ashok (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: Patient satisfaction is one of the most important indicators of the quality of emergency care. This hospital-based cross-sectional study was performed to assess patient satisfaction in the Emergency department of a tertiary care hospital and identify the factors associated. Methods: The study was performed on 785 patients visiting Emergency department. Variables under study were satisfaction level, triage score, waiting times, and socio-demographic characteristics. Satisfaction level was measured using a 5-point Likert scale, Cronbach’s alpha (α= 0.86 overall, inter-item α = 0.842-0.859). A score of 47 and above was cut off to denote satisfaction with a sensitivity of 75% and specificity of 81%. Descriptive analysis and Chi-square test was performed to see the association of variables of interests with patient satisfaction. A p-value <0.05 was considered statistically significant. Results: Median age of the patients was 47 years among which 51% were male. Medical emergencies were the most common problems reported (68.7%). The median (Q1, Q3, maximum) time to first contact with the doctor was 10 (5,15, 240) minutes. The patient satisfaction rate towards the Emergency services was 69%. Behavior of doctors (54%) and nurses’ care (44%) were rated as excellent services while poorer ratings were given for toilet condition (27%) and crowd control (14%). Weekends vs weekdays had a significant association with satisfaction (p = 0.04). Conclusion: Overall acceptable patient satisfaction rate was found in the services provided by the Emergency department. Areas needing improvement were identified.